2002
DOI: 10.1056/nejmoa010259
|View full text |Cite
|
Sign up to set email alerts
|

Gastropericardial Fistula after Laparoscopic Surgery for Reflux Disease

Abstract: APAROSCOPIC approaches are now commonly used to treat gastroesophageal reflux disease. 1,2 Many studies have demonstrated the safety, efficacy, and durability of these minimal-access procedures. 3 However, the learning curve for performing laparoscopic surgery in patients with reflux disease is steep, 4 and intraoperative complications can be life-threatening. 3 Reviews of long-term complications have shown that failed repairs (a "slipped wrap" or paraesophageal or hiatal hernia) can cause substantial morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Once identified, monitoring for progressive fluid accumulation and tamponade is essential. Potential mechanisms for the development of a pericardial effusion following gastrooesophageal surgery include: direct pericardial trauma, spread of infection from implanted prosthetic material and "sympathetic" pericarditis with effusion [5][6][7]. Sympathetic pericarditis may result from reactive pericardial inflammation in response to foreign material in close proximity to the pericardium and from pericardial trauma related to the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once identified, monitoring for progressive fluid accumulation and tamponade is essential. Potential mechanisms for the development of a pericardial effusion following gastrooesophageal surgery include: direct pericardial trauma, spread of infection from implanted prosthetic material and "sympathetic" pericarditis with effusion [5][6][7]. Sympathetic pericarditis may result from reactive pericardial inflammation in response to foreign material in close proximity to the pericardium and from pericardial trauma related to the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Complications secondary to infection or direct trauma such as pericardiotomy-like syndrome [5] and gastro-pericardial fistula [6] have been reported. Bui et al postulated "sympathetic" pericardial effusion secondary to an infected LAGB system in 2003 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hamid and coauthors identifi ed 95 cases (mean age, 54 years; range, 1-82) using a Medline search; their review demonstrated that the fi stulas originated from the stomach (46%), esophagus (38%), colon (11%), jejunum (2%), and duodenum (1%) (1). Fiftyfi ve cases developed after surgery, including esophagectomy (24 patients), fundoplication (14 patients, 6 postlaparoscopic), colonic interposition (8 patients), and diaphragmatic hernia repair Th e mortality rate is as high as 50% (5).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is much more likely in patients with prior gastroesophageal surgery, including laparoscopic Nissen fundoplication. F istula formation between the gastrointestinal tract and the pericardium is very uncommon and usually occurs after esophagogastric surgical procedures (1)(2)(3)(4)(5)(6)(7)(8). Laparoscopic Nissen fundoplication is the most common surgical treatment for gastroesophageal refl ux disease.…”
mentioning
confidence: 99%
“…7,8 The definite diagnosis of a gastro-pericardial fistula is achieved by performing several noninvasive imaging procedures, including chest X-rays that will show an enlarged mediastinum with fluid and air levels in the pericardial cavity.…”
Section: Discussionmentioning
confidence: 99%